Konsep Ibadah Dalam Islam: Telaah Teologis Dan Praktis - Suryani Ishak Djaree; Mursalin Muhmar (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This article discusses the concept of worship in Islam through two approaches: theological and practical. Theologically, worship is understood as the purpose of human creation and a form of total submission to God bound by the principles of sincerity and ittiba' (following the guidance of sharia). Practically, worship includes not only mahdhah (ritual) worship such as prayer, fasting, zakat, and hajj, but also ghairu mahdhah (non-ritual) worship in the form of social and professional activities that have the value of worship if they fulfill the requirements of intention, are halal (permissible) in nature, and bring benefits. Using a library study and thematic analysis of primary Islamic sources and literary concepts, this article demonstrates that worship is a framework for life (worldview) that integrates spiritual, moral, and social dimensions. The main findings confirm that the quality of worship is determined by its alignment with sharia, sincerity, and ethical impact on social life. This article recommends strengthening comprehensive worship literacy to build a Muslim character that is consistent between personal and social piety.